The effects of intravenous alfaxalone with and without premedication on intraocular pressure in healthy dogs - Bauer, Bianca S. (Can J Vet Res, 2016)
The objective of this study was to investigate the effects of intravenous alfaxalone with and without premedication on intraocular pressure (IOP) in healthy dogs. Thirty-three dogs were randomized to receive 1 of 3 treatments: acepromazine [0.03 mg/kg body weight (BW)] with butorphanol (0.2 mg/kg BW) intramuscularly (IM), followed by intravenous (IV) alfaxalone (1.5 mg/kg BW); dexmedetomidine (0.002 mg/kg BW) with hydromorphone (0.1 mg/kg BW) IM, followed by alfaxalone (1 mg/kg BW) IV; and saline 0.9% (0.02 mL/kg BW) IM, followed by alfaxalone (3 mg/kg BW) IV. Intraocular pressure (IOP) was measured at baseline, 15 min, and 30 min after premedication, after pre-oxygenation, after administration of alfaxalone, and after intubation. After induction and after intubation, the IOP was significantly increased in all groups compared to baseline. While premedication with acepromazine/butorphanol or dexmedetomidine/hydromorphone did not cause a significant increase in IOP, the risk of vomiting and the associated peak in IOP after dexmedetomidine/hydromorphone should be considered when selecting an anesthetic protocol for dogs with poor tolerance for transient increases in IOP.